2005
DOI: 10.1080/09540120412331299825
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a sexual health approach to reducing HIV/STD risk in the transgender community

Abstract: Despite reports of high prevalence of human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs) among the transgender community, very little prevention education has targeted this population. To fill this gap, we developed and evaluated a transgender-specific intervention, All Gender Health, which incorporates prevention strategies into comprehensive sexuality education. Transgender participants (N=181) attended the two-day seminar in community-based venues. The curriculum was delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 30 publications
3
61
0
2
Order By: Relevance
“…The remaining 14 studies reported data on MTF transgender women exclusively. Three studies evaluated behavioral interventions for transgender populations (Bockting et al 1999(Bockting et al , 2005Nemoto et al 2005).…”
Section: Description Of Reviewed Studiesmentioning
confidence: 99%
“…The remaining 14 studies reported data on MTF transgender women exclusively. Three studies evaluated behavioral interventions for transgender populations (Bockting et al 1999(Bockting et al , 2005Nemoto et al 2005).…”
Section: Description Of Reviewed Studiesmentioning
confidence: 99%
“…Transgender individuals may have an increased risk of HIV infection due to a range of factors. These include the effects of social stigma, such as shame, low selfesteem, secrecy, and loneliness (Bockting, Robinson, Forberg & Scheltema 2005), which can affect the negotiation of safer sexual practices and contribute to individuals engaging in higher risk sex (Bockting et al 2005).…”
Section: Why Does Gender Identity Matter For Hiv Risk?mentioning
confidence: 99%
“…1,5,[13][14][15] In April 2003, the Centers for Disease Control and Prevention (CDC) announced the Advancing HIV Prevention initiative, which was aimed at reducing barriers to early diagnosis of HIV infections and increasing access to quality medical care, treatment, and ongoing prevention services. 18 A key strategy of this initiative was to implement new models for diagnosing HIV infections outside of medical settings, with particular attention to diagnosing infections in minority populations and other communities that may have decreased access to or use of existing HIV testing services.…”
mentioning
confidence: 99%